(3OjhGf GdSQGL GdhQGbs - (3YeQ Hf eMeO Hf MSf, CHh MaU, SQGL GdOjf GdhQGb,J (B695 (3g` s
(3ChdgG (B:s
(3ef Cjf ddqOQ SfGc GdTQjb hddbfG gPG GdbhGe GdQTjb s
(3BNQgG (B:s
(3CNQLg CMeO hGdehUdj hGdWHQGfj ddKbGI GdQLGd ef WQb ajgG EVWQGH hdG JNdh ef GdVYa Ydi cd MGd s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B63 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B309s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B116 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI eYgO OejGW (B((3COH (B73) s
Keywords: (3GdCOHs